(3JHjjf GdMbGFb aj TQM cfR GdObGFbs - (3aNQ GdOjf CHh eMeO YKeGf Hf Ydj Hf eMLf GdRjdYj, YKeGf GdRjdYj,J (B743 (3g` s ((3eMeO Hf WGgQ GdMfai s)
(3ChdgG (B:s
(3cJGH GdeVGQHI gi TQcI HeGd ef LGfH hYed ef LGfH s
(3BNQgG (B:s
(3Je GdcJGH HMeO Gddgq s
(3GdcJGH GdeTQhM(B: (3cfR GdObGFb ddfSai GdeJhai (B710 (3g`s
(3HgG fXGe GdJYbjHIs
(3ai Chd GdfSNI agQSJ HehVhYGJ GdcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
Keywords: (3Gdabg GdMfajs